Residential Segregation and Integration: The Case of Zagreb (Dubrava) - Čaldarović, Ognjen (Array, 1997)
Major aspects of social integration and residential segregation are discussed on the example of Zagreb (Dubrava). It was concluded that patterns of social and residential segregation are not yet formed but that the signs of its formation are visible.